2012
DOI: 10.5754/hge12048
|View full text |Cite
|
Sign up to set email alerts
|

Current Situation of Endoscopic Treatment for Common Bile Duct Stones

Abstract: Common bile duct stones can be endoscopically treated safely with high rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Patients with cirrhosis have poor coagulation function and are at risk for bleeding; therefore, they require more care during surgery, resulting in longer operative times and an increased risk of postoperative pancreatitis. Studies have shown that cholangitis, coagulation disorders, cholecystectomy, history of jaundice, emergency procedures, intramural sphincter injection, sphincter pressure measurement, and biliary drainage are not risk factors for postoperative pancreatitis [13,14] . A controversial point is whether the experience of endoscopic operators is meaningful to the occurrence of pancreatitis after ERCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cirrhosis have poor coagulation function and are at risk for bleeding; therefore, they require more care during surgery, resulting in longer operative times and an increased risk of postoperative pancreatitis. Studies have shown that cholangitis, coagulation disorders, cholecystectomy, history of jaundice, emergency procedures, intramural sphincter injection, sphincter pressure measurement, and biliary drainage are not risk factors for postoperative pancreatitis [13,14] . A controversial point is whether the experience of endoscopic operators is meaningful to the occurrence of pancreatitis after ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that cholangitis, coagulation disorders, cholecystectomy, history of jaundice, emergency procedures, intramural sphincter injection, sphincter pressure measurement, and biliary drainage are not risk factors for postoperative pancreatitis. [ 13 , 14 ] A controversial point is whether the experience of endoscopic operators is meaningful to the occurrence of pancreatitis after ERCP. Notably, a lack of experience and a lower skill level of the operator will significantly increase the occurrence of errors and the risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The most effective and standard treatment for bile duct stones is endoscopic retrograde cholangiopancreatography (ERCP). [ 7 ] However, in 10% to 15% of cases, additional techniques are required, [ 8 ] typically due to a large stone size (>15 mm) and/or the tapering of the distal bile duct. Endoscopic papillary large balloon dilation (EPLBD), which consists of lithotomy without lithotripsy and dilation of the papilla using a large balloon, was first described by Ersoz et al [ 8 ] in 2013 as a technique to address challenging cases.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review has shown that, among patients with acute cholecystitis, the incidence of common bile duct stones varies from 2.4% to 25%, with an estimated pooled incidence of 13.7% [6] . The most effective and standard treatment for bile duct stones is endoscopic retrograde cholangiopancreatography (ERCP) [7] . However, in 10% to 15% of cases, additional techniques are required, [8] typically due to a large stone size (>15 mm) and/or the tapering of the distal bile duct.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) has become the first-choice treatment for common bile duct (CBD) disorders and periampullary disease 12. Compared with other endoscopic examinations, ERCP carries a higher potential for complications, ranging from minor events with prompt resolution, such as mild pancreatitis, to major life-threatening risks, such as hemorrhage and severe pancreatitis 34567.…”
Section: Introductionmentioning
confidence: 99%